Rapid solidification and metastable phase formation during surface modifications of composite Al-Cr cathodes exposed to cathodic arc plasma. (20th December 2021) - Golizadeh, Mehran; Mendez Martin, Francisca; Wurster, Stefan; Mogeritsch, Johann P.; Kharicha, Abdellah; Kolozsvári, Szilard; Mitterer, Christian; Franz, Robert
Graphical abstract: Image, graphical abstract Highlights: Modified layers on composite arc cathodes are formed by material intermixing in liquid state. Rapid solidification leads to the formation of metastable phases also including quasicrystals. Average cooling rate estimated to 10 6 K/s during solidification of the modified layer. Droplet redeposition contributes to material intermixing over larger distances. Powder grain size in composite arc cathodes influences microstructure and phase composition. Abstract: A combination of both conventional and advanced high-resolution characterization techniques was applied to study the modified layers on the surface of three composite Al-Cr arc cathodes with identical nominal composition of Al-50 at.% Cr but varying powder grain sizes. The results revealed that the modified layers consist mainly of metastable phases such as Cr solid solution, high temperature cubic Al8 Cr5, supersaturated Al solid solution, and icosahedral quasicrystal. The metastable phase formation indicates that high cooling rates were involved during the solidification of molten material produced in the arc craters during cathode spot events. The average cooling rate was estimated to be 10 6 K/s based on secondary dendrite arm spacing measurements and supporting phase-field based simulations. The formation mechanisms of the modified layers are discussed based on the obtained results and the current literature.